(3cJGH KGhPhSjhS aj GdfgGQ hGddjds - (3KGhPhSjhSs
(3ChdgG (B:s
(3GdTeS JJMQc MQcI eYJOdI VO MQcI Gdcd ai OGFQI hSW GdHQhL hgPg GdOGFQI TeS GdOGFQI GdTeSjI s
(3BNQgG (B:s
(3dGJUjQ ddTeS WdhY Ydi fbWg g` C HOkG hdG JQLY GdOhQGJ Edi eG cGfJ Ydjg CHOkG JeJ GdebGdI GdKGfjI ef cJGH KGhPhSjhS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3cJHJ Hbde eged GdfbXs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1401s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs